2011
DOI: 10.1053/j.gastro.2011.01.001
|View full text |Cite
|
Sign up to set email alerts
|

A Humanized Mouse Model to Study Hepatitis C Virus Infection, Immune Response, and Liver Disease

Abstract: Background & Aims-Studies of hepatitis C virus (HCV) infection, immunopathogenesis, and resulting liver diseases have been hampered by the lack of a small animal model. We developed humanized mice with human immune system and liver tissues to improve the studies of hepatitis C pathogenesis and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
299
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 274 publications
(311 citation statements)
references
References 40 publications
10
299
0
2
Order By: Relevance
“…It has been demonstrated that a human immune system and hepatocytes can be reconstituted in the same humanized mice (26). Similarly, we have shown previously that engraftment of CD34 + cells from fetal liver into NSG mice leads to reconstitution of human immune cells as well as human hepatocytes in the mouse liver (27).…”
Section: Discussionsupporting
confidence: 72%
“…It has been demonstrated that a human immune system and hepatocytes can be reconstituted in the same humanized mice (26). Similarly, we have shown previously that engraftment of CD34 + cells from fetal liver into NSG mice leads to reconstitution of human immune cells as well as human hepatocytes in the mouse liver (27).…”
Section: Discussionsupporting
confidence: 72%
“…Akute T cell leukemia (ATL) like T cell expansions [59] Dengue virus Leucocyte infection [66] Hepatitis C virus (HCV) Liver disease [69] John Cunningham (JC) virus Persistent infection [71] Influenza A virus Lung infection [72] 1 For clarity only one key reference has been listed Human fetal thymus and liver organoid…”
Section: Discussionmentioning
confidence: 99%
“…This was performed in BRG mice, in which liver damage was induced, by transfer of hepatocyte precursors and HPCs [68]. These mice were then infected with HCV intravenously [69]. Both HCV induced liver damage and induction of HCV specific immune responses could be observed.…”
Section: Flavivirus Infections (Dengue Virus Hcv)mentioning
confidence: 99%
“…Enfin, le système immunitaire de la souris doit être, lui aussi, humanisé, pour espérer reproduire toute la physiopathologie de la maladie. Ces différents critères semblent désormais réunis dans un modèle qui vient d'être publié dans la revue Gastroenterology [7]. L'animal receveur est une souris transgénique exprimant dans ses hépatocy-tes une caspase 8 dimérisable et donc L'infection de cette souris immunodé-primée par le VHC n'a été que récemment démontrée [6].…”
unclassified